2010
DOI: 10.1021/pr100389u
|View full text |Cite
|
Sign up to set email alerts
|

Differential Proteome of the Striatum from Hemiparkinsonian Rats Displays Vivid Structural Remodeling Processes

Abstract: Parkinson's disease is a multifactorial, neurodegenerative disease where etiopathogenetic mechanisms are not fully understood. Animal models like the neurotoxic 6-OHDA-hemiparkinsonian rat model are used for standardized experiments. Here, we analyzed proteome changes of the striatum three months after 6-OHDA lesions of the nigral dopaminergic cell population. Striata were removed and proteins were separated by 2DE followed by differential spot analysis. Proteins in spots were identified by MALDI-TOF-MS. Most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 128 publications
0
30
0
Order By: Relevance
“…VDAC1 protein and mRNA levels were reported to be elevated following administration of mitochondrial complex I inhibitors, such as rotenone and MPP ϩ (26,27). VDAC1 expression was also increased in striatal extracts of 6-hydroxydopamine-treated rats (35). Another study reported that VDAC1 protein level is elevated in the striatum and cortex of parkin null mice (36).…”
Section: Discussionmentioning
confidence: 99%
“…VDAC1 protein and mRNA levels were reported to be elevated following administration of mitochondrial complex I inhibitors, such as rotenone and MPP ϩ (26,27). VDAC1 expression was also increased in striatal extracts of 6-hydroxydopamine-treated rats (35). Another study reported that VDAC1 protein level is elevated in the striatum and cortex of parkin null mice (36).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, laser-captured motoneurons from presymptomatic mSOD1 mice showed a 30% decrease in CRT mRNA (Perrin et al, 2005) and reduced CRT protein levels are apparent in symptomatic mSOD1 spinal cord (Teuling et al, 2007). Moreover, CRT is downregulated in cortical neurons of Alzheimer's patient brains (Taguchi et al, 2000) and in striatal neurons of hemiparkinsonian rats (Lessner et al, 2010). Although no functional studies were carried out, it is striking that ER stress is activated in all the above contexts (Wang and Takahashi, 2007;Lee et al, 2010;Lessner et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CRT is downregulated in cortical neurons of Alzheimer's patient brains (Taguchi et al, 2000) and in striatal neurons of hemiparkinsonian rats (Lessner et al, 2010). Although no functional studies were carried out, it is striking that ER stress is activated in all the above contexts (Wang and Takahashi, 2007;Lee et al, 2010;Lessner et al, 2010). Reductions in CRT may therefore play a general role in neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…The extraction of proteins was performed according to published standardized protocols [26,30,31]. In the following the steps are described shortly.…”
Section: Homogenizationmentioning
confidence: 99%
“…Several studies [24][25][26] focus on the transplantation of immortalized progenitor cells in 6-OHDA Hemiparkinson animal models [24,25] and the differences in the abundance of this area of the brain at different points of development [26]. Hovakimyan et al [24] and Haas et al [25] as well as Schwarz and Freed [27] showed that the micro-environment of neonatal brains seems to be important for the differentiation of transplanted neuronal progenitors.…”
Section: Introductionmentioning
confidence: 99%